Preparation method of high-strength villiaumite with fluorinion release capability and application of villiaumite in 3D printing orthodontic appliance
By preparing high-strength fluorine salts with fluoride ion release ability, the problems of tooth demineralization and orthodontic white spots in the 3D printed orthodontic white spots during use are solved, the high strength and dimensional stability of the material are achieved, and the therapeutic effect of the orthodontic device is improved.
Patent Information
- Application Number
- CN202411885935.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing 3D printed orthodontic aligner materials are prone to cause dental demineralization and orthodontic white spots during use, and the strength and dimensional stability of the material are insufficient, affecting the treatment effect.
Using a high-strength fluorine salt with fluoride ion release ability, a 3D printing material with high strength and good fluoride ion release properties is prepared by reaction of tribenzylamine and halide, combined with acrylic resin and tetrafluoroboric acid.
This material provides extremely high strength and long-term use stability. At the same time, through excellent fluoride ion release ability, it effectively improves orthodontic white spots generated by dental demineralization and improves the smoothness of the surface of the appliance.
Smart Images

Figure CN119707719A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of 3D printing technology, and more specifically, to a method for preparing a high-strength fluoride salt having fluoride ion releasing ability and an application thereof in 3D printing orthodontic appliances. Background Art
[0002] In recent years, 3D printing technology has achieved rapid development, especially in the field of orthodontics. The emergence of 3D printing technology has solved the problems of long preparation cycle, low efficiency and high cost of traditional orthodontic dental molds, and promoted the rapid growth of the orthodontic industry market. Although 3D printing orthodontic dental molds is currently the mainstream technology, as an intermediate model material for the molding of customized braces, there are inevitably some problems, especially the deformation of the dental mold during the molding process, the high rate of bad parts during the tedious process of printing, cleaning and curing, and the trouble of the appliance demolding process. Compared with the complex operation of 3D printing dental molds and then using diaphragms for molding to obtain braces, direct 3D printing of braces is undoubtedly one of the efficient and simple technical solutions, and it is also one of the hot research and development directions of the current technology.
[0003] Traditional braces upstream products are all derived from orthodontic diaphragms. The diaphragm materials are currently common plastic materials, such as thermoplastic polyurethane (TPU), alcohol-modified polyethylene terephthalate (PETG): generally polyethylene terephthalate glycol 1,4-cyclohexane dimethanol ester, polyethylene terephthalate (PET), polypropylene (PP), polycarbonate (PC), etc. In the process of wearing braces, the relationship between teeth changes, and the braces will block the bristles of the toothbrush, making cleaning more difficult, food residues accumulate, and the oral flora is unbalanced. The closed environment caused by the braces will reduce the saliva around the teeth, which is not conducive to the self-cleaning effect of saliva, and reduce the content of calcium and phosphorus ions, weakening the remineralization efficiency, so orthodontic white spots will also occur. White spot lesions (WSL) refer to white spots that appear on the surface of teeth, which is a sign of decalcification or demineralization of tooth enamel. The caries produced after orthodontic treatment not only affects the appearance, but may also develop into severe caries, leading to the destruction of multiple tooth tissues and affecting the efficiency of tooth movement. It is a post-orthodontic complication worthy of attention.
[0004] At present, there is basically no concern about the problem of orthodontic white spots in the materials of 3D printed orthodontic appliances. Fluoride can reduce the solubility of tooth enamel and promote enamel remineralization. At the same acidity, if fluoride is present, the solubility of teeth is reduced and caries is less likely to occur. After micro-caries occur, exposure to fluoride can reverse caries to a certain extent. Fluoride can inhibit the growth of cariogenic bacteria in the mouth and inhibit bacterial acid production. Cariogenic bacteria decompose and metabolize food residues to produce acid, and the acid dissolves the minerals in the teeth to form caries. Fluoride has an inhibitory effect on this process. Conventional membrane and orthodontic products have been improved through coating and fluoride. However, since the fluoride additive is non-reactive, it will dissolve during the treatment cycle and cause surface defects, which will cause some tiny residues to exist in the defects, which will increase the risk of uneven tooth color and tooth decay. Therefore, the fluoride-containing composition should have good reactivity with 3D printing materials to increase the good chemical bonding force with the 3D printed orthodontic appliance, ensuring that it does not dissolve during the treatment process, which has a positive effect on biological rejection and treatment effect.
[0005] In orthodontic treatment, due to the long treatment cycle, the dimensional stability of the appliance during the treatment cycle is crucial to the final treatment effect. Therefore, the requirements for the non-deformation of 3D printed appliance materials are relatively strict. Therefore, 3D printing maintains high printing strength and non-deformation during the printing process and the treatment process, which are problems that need to be solved. In summary, adding a composition that can effectively improve the generation of orthodontic white spots to the 3D printed appliance material is of great significance for the treatment effect of orthodontic treatment. It should have the following three characteristics:
[0006] 1. High strength, maintaining a basically unchanged shape retention rate during use.
[0007] 2. Highly efficient fluoride ion release ability. Effectively improve orthodontic white spots caused by tooth demineralization.
[0008] 3. It has reactive groups that react with 3D printable materials, maintains a good bonding force with the 3D printing materials, and does not dissolve during the treatment cycle, thereby affecting the surface of the orthodontic appliance. Summary of the invention
[0009] In view of this, the present invention provides a method for preparing a high-strength fluoride salt with fluoride ion releasing ability to meet the high-strength and high-efficiency fluoride ion releasing performance, so as to be used for preparing 3D printed orthodontic material to meet the therapeutic effect.
[0010] The technical solution of the present invention is as follows:
[0011] The first aspect of the present invention is to provide a high-strength fluoride salt having the ability to release fluoride ions, having a structural formula shown in Formula I:
[0012]
[0013] Where R is C n H 2n , 1≤n≤3.
[0014] The second aspect of the present invention is to provide a method for preparing the high-strength fluoride salt described in the first aspect, the steps comprising:
[0015] S1. reacting tribenzylamine with a halide to obtain an intermediate 1;
[0016] S2. The obtained intermediate is reacted with an acrylic resin monomer under the action of an inhibitor to obtain an intermediate II;
[0017] S3. The intermediate 2 is reacted with tetrafluoroboric acid under reflux at 50-150° C. for 4-24 h to obtain a high-strength fluoride salt having the ability to release fluoride ions;
[0018] The halide has a structure shown in Formula II:
[0019]
[0020] Where R is C n H 2n , 1≤n≤3; X is a halogen.
[0021] Further, in step S1, the halide is selected from 2-(2-(chloromethyl)phenyl)ethylene oxide, 2-(3-(chloromethyl)phenyl)ethylene oxide, 2-(4-(chloromethyl)phenyl)ethylene oxide, 2-(4-(bromomethyl)phenyl)ethylene oxide, 2-(3-(bromomethyl)benzyl)ethylene oxide, 2-(4-(bromomethyl)benzyl)ethylene oxide, and 2-(2-(chloromethyl)phenethyl)ethylene oxide.
[0022] Furthermore, the molar ratio of the tribenzylamine to the halide is 1:(1-3); preferably 1:(1-1.5).
[0023] Furthermore, the solvent used in steps S1 to S3 is selected from one or more of hot ethanol, ether, chloroform, benzene, toluene, xylene, ether, dichloromethane, chloroform, acetate, 1,2-dichloroethane, 1,4-dioxane, tetrahydrofuran, acetone, butanone, cyclohexanone or N,N-dimethylformamide.
[0024] Further, in step S2, the polymerization inhibitor is selected from one or more of hydroquinone and its derivatives (2,5-di-tert-butylhydroquinone, 2-tert-butylhydroquinone), p-benzoquinone, methylhydroquinone, and p-hydroxyanisole;
[0025] And / or, the molar ratio of the intermediate 1 to the acrylic resin is 1:(1-3); preferably 1:(1-1.25).
[0026] Furthermore, in step S3, the molar ratio of the intermediate II to tetrafluoroboric acid is 1:(1-2.5).
[0027] The third aspect of the present invention is to propose the use of the high-strength fluoride salt described in the first aspect or the high-strength fluoride salt obtained by the preparation method described in the second aspect in the preparation of 3D printed orthodontic appliances.
[0028] Furthermore, the mass fraction of the high-strength fluoride salt added to the 3D printing material is 0.1-20%.
[0029] The fourth aspect of the present invention is to propose a 3D printing resin composition, which includes, by weight percentage: 0.1-20% of a monomer having a fluorine-releasing function, 80-99% of a photocurable monomer, and 1-3% of a photoinitiator; the monomer having a fluorine-releasing function is the high-strength fluoride salt described in the first aspect or the high-strength fluoride salt obtained by the preparation method described in the second aspect.
[0030] The fifth aspect of the present invention is to provide a 3D printed orthodontic appliance, which is obtained by 3D printing and curing the 3D printing resin composition described in the fourth aspect.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The high-strength fluoride salt of the present invention has four benzyl groups and at least one polymerizable reactive group, and contains a tetrafluoroboric acid structure, wherein the tetrabenzyl structure provides extremely high strength for the 3D printed appliance, the acrylate structure provides good long-term use stability for the 3D printed appliance, and the tetrafluoroboric acid structure provides excellent fluoride ion release ability for the 3D printed appliance, which can effectively improve orthodontic white spots caused by tooth demineralization.
[0033] The high-strength fluoride salt of the present invention can maintain good bonding strength when applied to 3D printing materials, and can be used to make orthodontic appliances to avoid dissolution during the treatment cycle and thus affect the product surface. While releasing fluoride ions, it can improve the surface smoothness and has significant application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of an appliance dental mold sample obtained by 3D printing in one embodiment of the present invention. DETAILED DESCRIPTION
[0035] The following are specific implementation examples of the present invention, which are preferred and detailed descriptions of the present invention. It should be understood that the specific implementation methods described in this specification are only for explaining the present invention, and are not intended to limit the present invention.
[0036] In one embodiment, a method for preparing a high-strength fluoride salt having the ability to release fluoride ions is provided, wherein the fluoride salt has a structural formula shown in Formula I:
[0037]
[0038] Where R is C n H 2n , n is a natural number and 1≤n≤3.
[0039] Contains four benzyl groups and at least one polymerizable reactive group, and contains a tetrafluoroboric acid structure. Specifically, the preparation method of the high-strength fluoride salt having the ability to release fluoride ions is as follows:
[0040] 1. Use tribenzylamine to react with halides, the general chemical formula of halides is C 9+a H 9+2a XO (a is 0-2), the halide is characterized by containing an epoxy group, a benzene ring structure and a halogen substituent. The molar ratio of tribenzylamine to the halide is 1:3, wherein in order to ensure the purity of the product, the preferred ratio is 1:1-1:1.15.
[0041] Wherein X is a halogen selected from I, Br or Cl; preferably Br or Cl. Preferred halides are 2-(2-(chloromethyl)phenyl)oxirane, 2-(3-(chloromethyl)phenyl)oxirane, 2-(4-(chloromethyl)phenyl)oxirane, 2-(4-(bromomethyl)phenyl)oxirane, 2-(3-(bromomethyl)benzyl)oxirane, 2-(4-(bromomethyl)benzyl)oxirane, 2-(2-(chloromethyl)phenethyl)oxirane.
[0042] Wherein, tribenzylamine is dissolved in a solvent (1 kg of solvent dissolves 1 mol of tribenzylamine), and the above reactants are stirred and refluxed in a temperature range of 80-180°C for a reaction time of 6-48 hours. After adding solvent for washing twice, a rotary evaporator is used in a water bath at 80°C and the speed is 200 r / min to remove excess reactants to obtain an intermediate product N1.
[0043] 2. The above N1 is dissolved in a solvent containing 1% of an inhibitor (1 kg of solvent dissolves 1 mol of N1 substance), and an acrylic acid resin monomer is added. The oxygen-containing heterocyclic ring is opened and reacts with acrylic acid to generate a reactive acrylic ester. The monomer containing an acrylic acid structure can be acrylic acid and methacrylic acid. After the reaction is stirred and refluxed, the excess solvent is removed by a rotary evaporation device to obtain the product N2. The molar ratio of N1 to (meth) acrylic acid resin is 1:1-1:3. In order to ensure the purity of the product, the preferred molar ratio is 1:1-1:1.25. The inhibitor is a mixture of one or more of hydroquinone and its derivatives (2,5-di-tert-butylhydroquinone, 2-tert-butylhydroquinone), p-benzoquinone, methylhydroquinone, and p-hydroxyanisole.
[0044] 3. The above N2 is dissolved in a solvent (1 kg of solvent dissolves 1 mol of N2 substance), and then tetrafluoroboric acid is added. After stirring and refluxing in a 50°C-150°C device for 4-24 hours, excess solvent is removed by rotary evaporation. The final product is obtained, wherein the molar ratio of N2 to tetrafluoroboric acid is 1:1-1:2.5.
[0045] The solvent may be one or more mixtures of hot ethanol, ether, chloroform, benzene, toluene, xylene, ether, dichloromethane, chloroform, acetate, 1,2-dichloroethane, 1,4-dioxane, tetrahydrofuran, acetone, butanone, cyclohexanone or N,N-dimethylformamide.
[0046] In the above embodiments, the tetrabenzyl structure contained in the high-strength fluoride salt with fluoride ion releasing ability provides extremely high strength for the 3D printed appliance, the acrylate structure provides good long-term use stability for the 3D printed appliance, and the tetrafluoroboric acid structure provides excellent fluoride ion releasing ability for the 3D printed appliance.
[0047] In the above embodiment, taking the reaction of 2-[4-(chloromethyl)phenyl]oxirane and tribenzylamine as an example, the specific synthesis route is as follows:
[0048]
[0049] In another embodiment, the application of the high-strength fluoride salt with fluoride ion release ability in the above embodiment in the field of 3D printing orthodontic appliances is proposed, which is specifically obtained by preparing a 3D printing composition and then 3D printing and light curing. Specifically, the content of each component of the 3D printing composition is within the following range:
[0050] (a) 0.1-20% by weight of high strength fluoride salt
[0051] (b) 80-99% by weight of photocurable monomer
[0052] (c) 1-3% by weight of photoinitiator
[0053] Since a universal functional material for 3D printing orthodontic appliances is prepared, the 3D printing resin composition monomers use aliphatic acrylate and 4-acryloylmorpholine as typical monomers to evaluate the material performance, and are not limited to other available monomers. The specific embodiments are evaluated using the following ratios:
[0054] (a) 0.1%-20% by weight of high strength fluoride salt
[0055] (b) 80-99% by weight of aliphatic polyurethane acrylate 50%, 4-acryloylmorpholine 40%
[0056] (c) 1-3% by weight of initiator
[0057] It is understandable that in the above 3D printing composition, the amount of high-strength fluoride salt required for preparing 3D printed orthodontic appliances can be selected in the range of 0.1%-20%, and can be selected specifically according to the required performance of the material. The greater the amount of addition, the more it promotes the release of fluoride ions and the strength of 3D printing. Therefore, under the premise of considering the performance of fluoride ion release and the strength of 3D printing, 2-20%, preferably 5-20%, and more preferably 5-15% can be selected.
[0058] In the above examples, the aliphatic polyurethane acrylate can be obtained from manufacturers such as Sartomer and Changxing. Sartomer CN8000 was used in this experiment, and 4-acryloylmorpholine was purchased from Merck Chemical.
[0059] The polymerization inhibitor used is one or more mixtures of hydroquinone and its derivatives (2,5-di-tert-butylhydroquinone, 2-tert-butylhydroquinone), p-benzoquinone, methylhydroquinone and p-hydroxyanisole.
[0060] In the above embodiments, the photoinitiator used for the photosensitive resin is one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide or a mixture thereof; the above inhibitors and photoinitiators are common raw materials and are purchased from McLean.
[0061] Specifically, in a preferred embodiment, the 3D printing process can be performed by pouring the above-mentioned photosensitive resin composition into the resin tank of the 3D printing DLP device for printing, with the printing parameters of 300mw and a single-layer curing time of 2.1s. A 100mm*12mm*2mm mechanical spline (universal mechanical testing machine) and a 10mm diameter, 1mm thick disc are printed to test the fluorine release, and a 50mm diameter, 10mm thick disc is printed to test the surface roughness.
[0062] In one embodiment, the above-mentioned photosensitive resin composition is 3D printed into a brace sample such as Figure 1 shown.
[0063] The following are preferred implementation examples. If the manufacturer of the reagent or instrument is not specified in the examples, conventional products can be purchased from the market. If the specific conditions are not specified, conventional conditions or conditions recommended by the manufacturer can be used.
[0064] Example 1
[0065] 1. Add 28.7 g (0.1 mol) of tribenzylamine dissolved in 100 g of methyl ether to a stirring reflux bottle, then add 16.8 g (0.1 mol) of 2-(2-(chloromethyl)phenyl)ethylene oxide, set the temperature to 80 ° C, and after 6 hours, pour the product into a rotary evaporator to remove excess reactants, then add xylene, wash twice, and continue to use rotary evaporation to remove excess solvent to obtain 37.4 g of white crystalline product.
[0066] 2. Take 22.8g (0.05mol) of the above white crystals and dissolve them in 50g of acetone (containing 1% hydroquinone) solvent in a reflux stirring device under 80°C water bath conditions, slowly add 3.6g (0.05mol) of acrylic acid, and take samples for testing until the epoxy group is 1120cm -1 The infrared peak of the band disappeared. The excess acrylic acid and solvent were removed by rotary evaporation to obtain 25.8 g of white crystals.
[0067] 3. 20.6 g (0.04 mol) of the above product was dissolved in 40 g of 1,2-dichloroethane, 3.5 g (0.04 mol) of tetrafluoroboric acid was added, and the mixture was reacted at 70°C in a stirring reflux bottle for 4 h. The mixture was transferred to a rotary evaporator to remove excess solvent to obtain the final product.
[0068] 4. Prepare a 3D printing resin composition according to the following proportions: 5% (10 g) of the above product, 50% (100 g) of aliphatic acrylate, 42% (84 g) of 4-acryloylmorpholine, and 3% (6 g) of initiator, and stir at 2000 r / min for 2 min using a high-speed disperser.
[0069] Example 2
[0070] 1. Add 28.7 g (0.1 mol) of tribenzylamine to a stirring reflux bottle and dissolve it in 100 g of methyl ether, then add 23.6 g (0.14 mol) of 2-(3-(chloromethyl)phenyl)ethylene oxide, set the temperature to 180 ° C. After 48 hours, pour the product into a rotary evaporator to remove excess reactants, then add solvent, wash twice, and continue to use rotary evaporation to remove excess solvent to obtain 45.2 g of white crystalline product.
[0071] 2. Take 22.8g (0.05mol) of the above white crystals and dissolve them in 50g of cyclohexanone (containing 1% hydroquinone) solvent in a reflux stirring device under 80°C water bath conditions, slowly add 5.4g (0.0625mol) of methacrylic acid, and take samples for testing until the epoxy group is 1120cm -1 The infrared peak of the band disappeared. The excess methacrylic acid and solvent were removed by rotary evaporation to obtain 25.1 g of white crystals.
[0072] 3. 21.7 g (0.04 mol) of the above product was dissolved in 40 g of tetrahydrofuran, and 3.5 g (0.04 mol) of tetrafluoroboric acid was added. The mixture was reacted at 150° C. in a stirring reflux bottle for 24 h, and then transferred to a rotary evaporator to remove excess solvent to obtain the final product.
[0073] 4. Prepare a 3D printing resin composition according to the following proportions: 5% (10 g) of the above product, 50% (100 g) of aliphatic acrylate, 42% (84 g) of 4-acryloylmorpholine, and 3% (6 g) of initiator, and stir at 2000 r / min for 2 min using a high-speed disperser.
[0074] Example 3
[0075] 1. Add 57.4g (0.2mol) of tribenzylamine to a stirring reflux bottle and dissolve it in 100g of chloroform, then add 100.8g of 2-(4-(chloromethyl)phenyl)ethylene oxide, set the temperature to 120°C, after 12h, set the speed to 200r / min, pour the product into a rotary evaporation bottle, remove excess reactants, then add solvent, wash twice, continue to use rotary evaporation to remove excess solvent, and obtain 80.4g of white crystalline product.
[0076] 2. Take 45.6g (0.1mol) of the above white crystals and dissolve them in 100g of N,N-dimethylformamide (containing 1% hydroquinone) solvent in a reflux stirring device under 80°C water bath conditions, slowly add 7.2g (0.1mol) of acrylic acid, and take samples for testing until the epoxy group is 1120cm -1 The infrared peak disappeared, and the excess methacrylic acid and solvent were removed by rotary evaporation to obtain 48.4 g of white crystals.
[0077] 3. 43.4 g (0.08 mol) of the above product was dissolved in 80 g of ethanol, and 7 g (0.08 mol) of tetrafluoroboric acid was added. The mixture was reacted at 90° C. for 12 h in a stirring reflux bottle, and then transferred to a rotary evaporator to remove excess solvent to obtain the final product.
[0078] 4. Prepare a 3D printing resin composition according to the following proportions: 20% (40 g) of the above product, 35% (70 g) of aliphatic acrylate, 42% (84 g) of 4-acryloylmorpholine, and 3% (6 g) of initiator, and stir at 2000 r / min for 2 min using a high-speed disperser.
[0079] Example 4
[0080] 1. Add 28.7g (0.1mol) of tribenzylamine to a stirring reflux bottle and dissolve it in 100g of butanone, then add 33.3g (0.1mol) of 2-(4-(bromomethyl)phenyl)ethylene oxide, set the temperature to 120°C, and after 12h, pour the product into a rotary evaporator to remove excess reactants, then add solvent, wash twice, and continue to use rotary evaporation to remove excess solvent to obtain 50.9g of white crystalline product.
[0081] 2. Take 25g (0.05mol) of the above white crystals and dissolve them in 50g of acetone (containing 1% hydroquinone) solvent in a reflux stirring device under 80°C water bath conditions, slowly add 10.8g (0.15mol) of acrylic acid, and take samples for testing until the epoxy group is 1120cm -1 The infrared peak disappeared, and the excess methacrylic acid and solvent were removed by rotary evaporation to obtain 27.8 g of white crystals.
[0082] 3. 22.3 g (0.04 mol) of the above product was dissolved in 40 g of ethyl acetate, 4.4 g (0.05 mol) of tetrafluoroboric acid was added, and the mixture was reacted at 50° C. for 4 h in a stirring reflux bottle, and then the mixture was transferred to a rotary evaporator to remove excess solvent to obtain the final product.
[0083] 4. Prepare a 3D printing resin composition according to the following proportions: 2% (4 g) of the above product, 53% (106 g) of aliphatic acrylate, 42% (84 g) of 4-acryloylmorpholine, and 3% (6 g) of initiator, and stir at 2000 r / min for 2 min using a high-speed disperser.
[0084] Example 5
[0085] 1. Add 57.4g (0.2mol) of tribenzylamine to a stirring reflux bottle and dissolve it in 200g of butanone, then add 42g (0.23mol) of 2-(2-(chloromethyl)phenethyl)ethylene oxide, set the temperature to 100°C, and after 6h, pour the product into a rotary evaporator to remove excess reactants, then add solvent, wash twice, and continue to use rotary evaporation to remove excess solvent to obtain 77g of white crystalline product.
[0086] 2. Take 47g (0.1mol) of the above white crystals and dissolve them in 100g of toluene (containing 1% hydroquinone) solvent in a reflux stirring device under 80°C water bath conditions, slowly add 9.6g (0.125mol) of acrylic acid, and take samples for testing until the epoxy group is 1120cm -1 The infrared peak of the band disappeared. The excess acrylic acid and solvent were removed by rotary evaporation to obtain 54.2 g of white crystals.
[0087] 3. 42.2 g (0.08 mol) of the above product was dissolved in 80 g of ethanol, and 8 g (0.09 mol) of tetrafluoroboric acid was added. The mixture was reacted in a stirring reflux bottle at 70° C. for 4 h, and then transferred to a rotary evaporator to remove excess solvent to obtain the final product.
[0088] 4. Prepare a 3D printing resin composition according to the following proportions: 15% (30 g) of the above product, 40% (80 g) of aliphatic acrylate, 42% (84 g) of 4-acryloylmorpholine, and 3% (6 g) of initiator, and stir at 2000 r / min for 2 min using a high-speed disperser.
[0089] Comparative Example 1
[0090] 1. Add 10.1 g (0.1 mol) of triethylamine and dissolve it in 100 g of methyl ether in a stirring reflux bottle, then add 16.8 g (0.1 mol) of 2-(2-(chloromethyl)phenyl)ethylene oxide, set the temperature to 120 ° C, and after 12 hours, pour the product into a rotary evaporator to remove excess reactants, then add solvent, wash twice, and continue to use rotary evaporation to remove excess solvent to obtain 22.6 g of white crystalline product.
[0091] 2. 13.5 g (0.05 mol) of the above product was dissolved in 40 g of ethanol, 4.4 g (0.05 mol) of tetrafluoroboric acid was added, and the mixture was reacted at 70° C. in a stirring reflux bottle for 4 h. The mixture was transferred to a rotary evaporator to remove excess solvent to obtain the final product.
[0092] 3. Prepare a 3D printing resin composition according to the following proportions: 5% (10 g) of the above product, 50% (100 g) of aliphatic acrylate, 42% (84 g) of 4-acryloylmorpholine, and 3% (6 g) of initiator, and stir at 2000 r / min for 2 min using a high-speed disperser.
[0093] Comparative Example 2
[0094] A 3D printing resin composition was prepared according to the following proportions: 5% (10 g) of sodium fluoride, 50% (100 g) of aliphatic acrylate, 42% (84 g) of 4-acryloylmorpholine, and 3% (6 g) of initiator, and stirred at 2000 r / min for 2 min using a high-speed disperser.
[0095] Comparative Example 3
[0096] 1. Add 10.1 g (0.1 mol) of triethylamine and dissolve it in 100 g of methyl ether in a stirring reflux bottle, then add 16.8 g (0.1 mol) of 2-(2-(chloromethyl)phenyl)ethylene oxide, set the temperature to 120 ° C, and after 12 hours, pour the product into a rotary evaporator to remove excess reactants, then add solvent, wash twice, and continue to use rotary evaporation to remove excess solvent to obtain 22.6 g of white crystalline product.
[0097] 2. Take 13.5g (0.05mol) of the above white crystals and dissolve them in 50g of acetone (containing 1% hydroquinone) solvent under 80°C water bath conditions in a reflux stirring device, slowly add 3.6g (0.05mol) of acrylic acid, and take samples for testing until the epoxy group is 1120cm -1 The infrared peak of the band disappeared. The excess acrylic acid and solvent were removed by rotary evaporation to obtain 15.3 g of white crystals.
[0098] 3. 13.1 g (0.04 mol) of the above product was dissolved in 40 g of ethanol, 3.5 g (0.04 mol) of tetrafluoroboric acid was added, and the mixture was reacted at 150° C. in a stirring reflux bottle for 24 h. The mixture was transferred to a rotary evaporator to remove excess solvent to obtain the final product.
[0099] 4. Prepare a 3D printing resin composition according to the following proportions: 5% (10 g) of the above product, 50% (100 g) of aliphatic acrylate, 42% (84 g) of 4-acryloylmorpholine, and 3% (6 g) of initiator, and stir at 2000 r / min in a high-speed disperser for 2 min.
[0100] Experimental example
[0101] The photosensitive resin compositions obtained in the above Examples 1-5 and Comparative Examples 1-3 were poured into the resin tank of the 3D printing equipment for printing. The printing parameters were 300mw and the single-layer curing time was 2.1s. A mechanical strip of 100mm*12mm*2mm (universal mechanical testing machine) and a disc of 10mm diameter and 1mm thickness were printed to test the fluorine release. A disc of 50mm diameter and 10mm thickness was printed to test the surface roughness. The printing strength (Mpa), maximum fluorine release (ng·mm -2 ·d -1 ), 30-day cumulative fluoride release (ng·mm -2 ) and surface roughness (Ra).
[0102] Fluoride release test method:
[0103] Each sample is immersed in 5g of deionized water, and the fluoride ion content of the leachate is determined by a fluoride ion selective electrode. The fluoride ion content is measured every day from 1 to 30 days, and the maximum fluoride release within 30 days is calculated and the cumulative fluoride release within 30 days is calculated. The fluoride release test method is in accordance with GB 7484-87 "Determination of fluoride in water quality by ion selective electrode method", and the equipment used is Shanghai Leixie PXSJ-216F ion meter.
[0104] Surface roughness test:
[0105] The surface of the test disc was polished to Ra = 0.1, and soaked in 100g of deionized water. The sample was taken out after 30 days, and the test surface was wiped dry and tested for roughness using a surface roughness meter.
[0106] The test results are shown in Table 1.
[0107] Table 1:
[0108] test Print Strength Maximum fluoride release Cumulative fluoride release in 30 days Surface roughness unit Mpa <![CDATA[ng·mm -2 ·d -1 ]]> <![CDATA[ng·mm -2 ]]> Ra Example 1 45.3 25.3 351.4 0.1 Example 2 44.5 21.4 320.8 0.1 Example 3 52.1 67.1 987.1 0.1 Example 4 40.1 12.4 225.1 0.1 Example 5 48.7 51.0 725.8 0.1 Comparative Example 1 30.1 45.1 509.1 3.5 Comparative Example 2 31.4 78.1 875.3 4.0 Comparative Example 3 34.1 34.4 401.1 0.1
[0109] It is not difficult to see from Table 1 that Examples 1-5 have obvious advantages in printing strength, fluoride ion release and surface smoothness by adding materials with high-strength fluoride salts having fluoride ion release ability.
[0110] Compared with Examples 1-3, the surfaces of the synthesized fluorides in Comparative Examples 1 and 2 became rough after being soaked in water for 30 days, indicating that the high-strength fluoride salt has the function of releasing fluorine while ensuring the smoothness of the surface.
[0111] Compared with Example 1, the synthesized fluoride in Comparative Example 3 does not contain a tetrabenzyl group, and its strength in the 3D printing composition is significantly reduced, indicating that the synthesized high-strength fluoride salt has enhanced the strength of the material due to its tetrabenzyl structure.
[0112] Examples 3, 4 and 5 show that the synthesized high-strength fluoride salt has good fluoride release ability and has good fluoride release ability at different addition amounts, and can be added in proportion according to actual fluoride release requirements.
[0113] Finally, a few points should be explained. Although the present invention has been described in detail above with general descriptions and specific embodiments, on the basis of the present invention, the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-strength fluoride salt having the ability to release fluoride ions, characterized in that: It has the structural formula shown in Formula I: Where R is C n H 2n , 1≤n≤3.
2. The method for preparing the high-strength fluoride salt according to claim 1, characterized in that the steps include: S1. reacting tribenzylamine with a halide to obtain an intermediate 1; S2. The obtained intermediate is reacted with an acrylic resin monomer under the action of an inhibitor to obtain an intermediate II; S3. The intermediate 2 is reacted with tetrafluoroboric acid under reflux at 50-150° C. for 4-24 h to obtain a high-strength fluoride salt having the ability to release fluoride ions; The halide has a structure shown in Formula II: Where R is C n H 2n , 1≤n≤3; X is a halogen.
3. The preparation method according to claim 2, characterized in that: In step S1, the halide is selected from 2-(2-(chloromethyl)phenyl)ethylene oxide, 2-(3-(chloromethyl)phenyl)ethylene oxide, 2-(4-(chloromethyl)phenyl)ethylene oxide, 2-(4-(bromomethyl)phenyl)ethylene oxide, 2-(3-(bromomethyl)benzyl)ethylene oxide, 2-(4-(bromomethyl)benzyl)ethylene oxide, and 2-(2-(chloromethyl)phenethyl)ethylene oxide.
4. The preparation method according to claim 2, characterized in that: The molar ratio of tribenzylamine to halide is 1:(1-3); preferably 1:(1-1.5).
5. The preparation method according to claim 2, characterized in that: The solvent used in steps S1 to S3 is selected from one or more of hot ethanol, ether, chloroform, benzene, toluene, xylene, ether, dichloromethane, chloroform, acetate, 1,2-dichloroethane, 1,4-dioxane, tetrahydrofuran, acetone, butanone, cyclohexanone or N,N-dimethylformamide.
6. The preparation method according to claim 2, characterized in that: In step S2, the polymerization inhibitor is selected from one or more of hydroquinone and its derivatives (2,5-di-tert-butylhydroquinone, 2-tert-butylhydroquinone), p-benzoquinone, methylhydroquinone, and p-hydroxyanisole; And / or, the molar ratio of the intermediate 1 to the acrylic resin is 1:(1-3); preferably 1:(1-1.25).
7. The preparation method according to claim 2, characterized in that: In step S3, the molar ratio of the intermediate II to tetrafluoroboric acid is 1:(1-2.5).
8. Use of the high-strength fluoride salt according to claim 1 or the high-strength fluoride salt obtained by the preparation method according to any one of claims 2 to 7 in the preparation of 3D printed orthodontic appliances.
9. A 3D printing resin composition, characterized in that: The components include, by weight percentage: 0.1-20% of a monomer having a fluorine-releasing function, 80-99% of a photocurable monomer, and 1-3% of a photoinitiator; The monomer having the fluorine-releasing function is the high-strength fluoride salt described in claim 1 or the high-strength fluoride salt obtained by the preparation method described in any one of claims 2-7. 10.3D printed orthodontic appliance, characterized in that: The 3D printing resin composition according to claim 9 is 3D printed and cured.
Citation Information
Patent Citations
Force-responding polymer foam composite
CN111171365A
Composition based on acrylic acid liquid crystal photosensitive resin and application of composition in 405-nm 3D printing
CN113651920A
Self-healing and 3D printing ionic gel as well as preparation and application thereof
CN113801272A
Polishing compositions and methods with high selectivity for silicon nitride and polysilicon with respect to silicon oxide
CN114599753A
Cited By
PH response type MOF material, composite photosensitive resin system containing same and application of pH response type MOF material in dental appliance
CN121975065A